2008
DOI: 10.1002/ejic.200800849
|View full text |Cite
|
Sign up to set email alerts
|

Transition Metal Complexes of N‐Heterocyclic Germylenes

Abstract: The five-membered N-heterocyclic germylenes (NHGe) 1a-3a, with or without benzo or naphtho anellation, react with [Mo(CO) 3 (cht)] (cht = 1,3,5-cycloheptatriene) to form the fac-[(NHGe) 3 Mo(CO) 3 ] complexes 1b-3b. Similarly, [Ni(bnNHGe) 4 ] was obtained from the benzo-anellated germylene (bnNHGe) and Ni(1,5-cod) 2 ; attempts to synthesize less electron-rich complexes with mono-or divalent transition metals failed. The CO valence vibrations in the IR spectra of 1b-3b, together with their short Ge II -Mo bonds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(31 citation statements)
references
References 58 publications
2
29
0
Order By: Relevance
“…Silylenes and germylenes [71][72][73][74][75][76][77][78][79][80][81][82][83][84], the heavier analogues of carbenes [85][86][87], are important species in numerous thermal and photochemical reactions . Similar to carbenes, most of silylenes and germylenes can function as Lewis acid or Lewis base, in which the vacant p orbital is responsible for electrophilic character (Lewis acid), while the non-bonding electron pair can act as the nucleophilic (Lewis base) attack region [77].…”
Section: Introductionmentioning
confidence: 99%
“…Silylenes and germylenes [71][72][73][74][75][76][77][78][79][80][81][82][83][84], the heavier analogues of carbenes [85][86][87], are important species in numerous thermal and photochemical reactions . Similar to carbenes, most of silylenes and germylenes can function as Lewis acid or Lewis base, in which the vacant p orbital is responsible for electrophilic character (Lewis acid), while the non-bonding electron pair can act as the nucleophilic (Lewis base) attack region [77].…”
Section: Introductionmentioning
confidence: 99%
“…However, for the higher homologues, N-heterocyclic silylenes NHSi [84][85][86][87][88][89] and germylenes NHGe [26,90,91] the occurrence is far more frequent and appears to be the rule for annelated NHSi and NHGe. In a recent publication, Ullah et al [92]. The authors concluded that the delocalised -electron system in the five-membered ring features a reduced heteroaromatic stabilisation that enables bending, but that actual bending is triggered by steric factors, i.e.…”
Section: Complexes With Bent Nhcmentioning
confidence: 97%
“…Although, NHGe are generally expected to be more stable than their carbene analogues [2,6,7] and for the same reasons that GeCl 2 is more stable than CCl 2 [1,8], the stability and reactivity of NHGe can be significantly modified by substitution and annelation [9][10][11] to an extent where the reactivity is reversed and the NHGe acts as a Lewis acid [11].…”
Section: Theoretical Developmentsmentioning
confidence: 99%
“…An interesting topic in recent years has been the influence of annelation on the electronic properties of the NHGe ligand [4,9,11,12,18] and its ligating ability [10,11,42,43].…”
Section: Meller Germylenes [4041]mentioning
confidence: 99%